HISTORICAL TRACES OF JAVANESE SCRIPT: ANALYSIS OF DEVELOPMENT AND CULTURAL ROLE - Fifi Fatha; Muhammad Ray Jhon; Sarah Clarissa Hutagalung; Syahrani; Asini Rohana Silaban; Flores Tanjung (RADJA PUBLIKA, 2025)
Javanese script, better known as Hanacaraka, is one of the many cultural achievements of Indonesia's ancestors. Over time, Javanese script seems to be one of the forgotten cultural achievements. As the young generation of Indonesia, we should preserve the nation's culture which is a legacy of our ancestors. For this reason, research on the historical traces of Javanese script was conducted to show the dynamics of development and the role of culture in the writing system that has become an inseparable part of the identity of the Javanese community. This research uses a qualitative approach by analyzing historical sources in the form of ancient manuscripts, inscriptions, and cultural artifacts that illustrate the transformation of Javanese writing from the royal period to the modern period.